The Potential Use of the CRISPR-Cas System for HIV-1 Gene Therapy - Gabriela De Nardi Sanches-da-Silva; Luiza Fonseca Sales Medeiros; Fabio Mitsuo Lima (International Journal of Genomics)
The HIV-1 virus (human immunodeficiency virus) affects 36.9 million people worldwide, with approximately 900000 deaths in 2017. The virus carrier can develop severe immunodeficiency since CD4+ T lymphocytes are the main target, leading to acquired immunodeficiency syndrome (AIDS). Despite advances in pharmacological treatment, it is still difficult to eliminate latent reservoirs, becoming one of the main obstacles for viral eradication. The CRISPR- (clustered regularly interspaced short palindromic repeat-) Cas system is a genome-editing method which uses a guide RNA, a complementary sequence to the interested site, recruiting a nuclease that can break the viral or the host cell genetic material. From this double-stranded break, cellular repair mechanisms are activated being able to generate deletions, insertions, or substitutions, in order to inactivate specific gene loci, leading to loss of function. The objective of this minireview is to synthesize the current knowledge on the application of CRISPR-Cas-based gene therapy for HIV-1. The strategies encompass all steps of the viral infection cycle, from inhibition of cell invasion, through viral replication and integration inhibition, to excision of the latent provirus. Off-target effects and ethical implications were also discussed to evaluate the safety of the approach and viability of its application in humans, respectively. Although preclinical and clinical tests are still needed, the recent results establish an exciting possibility of applying this technology for prophylaxis and treatment of HIV-1.